The scope of hospital medicine practice at night: a national survey of night shift hospitalists. Issue 4 (8th August 2021) - Atlas, Kathleen R.; Forbes, Meggan; Riches, Jamie; Maina, Elizabeth; Lim, Richard; Johnson, Timothy; Niessen, Timothy; Desai, Neil
ABSTRACT: Introduction : Although in-person hospitalist presence, increasingly staffed by dedicated nocturnists, has become the norm overnight in the hospital, the scope of nocturnist practice and typical workload has not been defined. This study examines the clinical responsibilities and patient safety perceptions of hospitalists who work night shifts in the United States. Methods : In the fall of 2019, a cross-sectional, web-based survey was administered to physician and nurse practitioner/physician assistant (NP/PA) hospitalists who work night shifts. The questionnaire assessed night staffing structure, typical responsibilities, patient volume, perceptions of safety overnight, as well as demographic information. The survey was posted on the Society of Hospital Medicine (SHM) Hospital Medicine Exchange (HMX) Online Discussion Forum. Additionally, the survey was distributed by 'snowball method' by respondents to other night hospitalists. Responses were collected anonymously. Results : Of the 167 respondents, 157 reported working night shifts. There was at least one respondent from 32 different states. In addition to performing admissions to medicine services and covering inpatients, night hospitalists cover ICU patients, participate in RRT/Code teams and procedure teams, perform consults, participate in medical education, and take outpatient calls. Across institutions, there was a large distribution in numbers of patients covered in a night shift; however, patient volume fell into typical ranges: 5–10 admissions for physicians, 0–6 admissions for NP/PAs, and 25–75 patient cross-coverage census. When physicians perform more than five admissions per night, hospitalists were less likely to agree that they could provide safe care (88% vs. 63%, p = 0.0006). Conclusions : This is the first national study to examine the clinical responsibilities of hospitalists working overnight. Overnight responsibilities are heterogeneous across institutions. As hospitals are increasingly employing nocturnists, more research is needed to guide night staffing and optimize patient safety.